Postoperative Hemiplegic Migraine After a Laparoscopic Cholecystectomy: A Case Report. Issue 7 (1st April 2017) - Happel, Joseph; Quiko, Albin S.; Phun, Huy; Collier, Martin; Mortensen, Amy
Abstract : We report the case of a 35-year-old woman who developed severe right-sided hemiplegia and hemisensory loss shortly after emergence from general anesthesia for a laparoscopic cholecystectomy. Her medical history was significant for migraine with aura and a family history of transient hemiparesis thought to be a result of a transient ischemic attack. The patient's deficits slowly resolved, and she was ultimately diagnosed with familial hemiplegic migraine after a negative workup for cerebrovascular accidents.